2004
DOI: 10.1177/0263276404046070
|View full text |Cite
|
Sign up to set email alerts
|

Doing Office Work on the Motorway

Abstract: This article takes the motorway seriously as a place where the society of traffic can be found and studied. While many kinds of activities are done by drivers and passengers in parallel with driving on the motorway, such as listening to the radio, eating lunch or caring for, or being, children, I focus here on office work. Empirical material from a video-ethnography of one driver doing paperwork and overtaking a slow-moving vehicle ahead is used to examine in detail some of the practices of combining driving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(115 citation statements)
references
References 22 publications
3
106
0
6
Order By: Relevance
“…Feminist geographers have long observed that women have the primary responsibility for organising and undertaking care, for children and others (Laurie et al, 1999, McKie et al, 2002. In my research, in just under half of two parent families (46%), mothers had the sole responsibility for caring for children whilst they travelled.…”
Section: Mapping Gendered Geographies Of Care and The Escort Of Childrenmentioning
confidence: 99%
“…Feminist geographers have long observed that women have the primary responsibility for organising and undertaking care, for children and others (Laurie et al, 1999, McKie et al, 2002. In my research, in just under half of two parent families (46%), mothers had the sole responsibility for caring for children whilst they travelled.…”
Section: Mapping Gendered Geographies Of Care and The Escort Of Childrenmentioning
confidence: 99%
“…In this respect the car is frequently represented as a kind of cocoon that, variously enables the mobile reproduction of erstwhile static private domestic (Laurier et al, 2008), occupational (Laurier, 2004) and, of course, sensory spaces.…”
Section: Automobility and The Sensesmentioning
confidence: 99%
“…Further, the typically small and homogeneous population sizes they examine means there are limits to their generalizability. For example, Hislop & Axtell (2009) report the findings of a qualitative study on some management consultants, while Laurier (2004) analyzes the travel behaviours of a single worker.…”
Section: The Growing Importance Of Business Travelmentioning
confidence: 99%